Myrtle Oak, Quercus myrtifolia - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Myrtle oak is one of the three scrub oaks characteristic of scrub communities. It occurs on coastal regions of the Florida Panhandle and throughout the Florida peninsula and coastal southeastern United States west to Mississippi and east to South Carolina. The acorns of myrtle oak are an important food source for wildlife. https://edis.ifas.ufl.edu/sg183